Colours and attention in FMCG retail: An eye-tracking study of new information on shelf labels - Lázár, Erika; Németh, Péter; Bakó, Lili (Vezetéstudomány / Budapest Management Review, 2026)
The contemporary retail environment has led to a notable shift towards an intense sensory and emotional experience for consumers during the shopping process. This highlights the necessity of investigating the impact of these stimuli on consumer decision-making, which frequently occurs unconsciously. From a research perspective, visual stimuli and the underlying neurobiological processes of their perception are of particular significance, warranting investigation using eyetracking methodologies. The results of an eye-tracking experiment conducted with a sample of 90 participants (divided into three groups) demonstrate the critical role of colours in conveying additional information presented on shelves in retail environments. Among the stimulus materials used in the study, information with colour coding was able to produce a significant change in the participants’ attention during the time spent processing information.CORRECTION: https://journals.lib.uni-corvinus.hu/index.php/vezetestudomany/article/view/2405/1879